Effect of insulin resistance on whole blood mRNA and microRNA expression affecting bone turnover - Razny, Urszula; Polus, Anna; Goralska, Joanna; Zdzienicka, Anna; Gruca, Anna; Kapusta, Maria; Biela, Maria; Dembinska-Kiec, Aldona; Solnica, Bogdan; Malczewska-Malec, Malgorzata (European journal of endocrinology, 2019)
Objective To evaluate the effect of insulin resistance in obesity on the expression in whole blood of mRNA and miRNA affecting bone homeostasis as well as to estimate the influence of oral glucose load (OGTT) on serum osteocalcin concentration in obese individuals with and without insulin resistance. Design Cross-sectional study. Methods Carboxylated (cOC), undercarboxylated (ucOC) and total osteocalcin were measured by ELISA in the serum of obese subjects with insulin resistance (n = 41) and obese subjects without insulin resistance (n = 41) (control group) during OGTT. Analysis of gene expression (microarray) and miRNAs (real-time PCR) was performed in venous blood (representating samples) collected before OGTT from obese with insulin resistance and controls. Results Obese subjects with insulin resistance (higher HOMA-IR and lower oral glucose insulin sensitivity index) presented significantly increased expression of WNT signalling inhibitors (DKK1, DKK2, SOST, SFRP1) and downregulation of the key factor in WNT signalling – β catenin participating in osteoblasts differentiation. Expression of miRNA involved in osteoblastogenesis was also inhibited (miR-29b, miR-181a, miR-210, miR-324-3p). During OGTT, contrary to the control group, subjects with insulin resistance presented suppression of cOC and total OC decrease after 1 and 2 h of oral glucose load. Conclusions Obese subjects with insulin resistance may have defects in osteoblastogenesis that was demonstrated via key signalling molecules mRNA downregulation, and increased expression of WNT antagonists as well as inhibition of expression of miRNA participating in the regulation of osteoblast differentiation. Disturbed osteoblastogenesis in insulin-resistant subjects results in the suppression of blood carboxylated and total osteocalcin decrease during OGTT.